ЭКОЛОГИЧЕСКИЕ ПРОБЛЕМЫ И ИНСТРУМЕНТЫ ФИНАНСОВО- ИНВЕСТИЦИОННОГО МЕХАНИЗМА ПО РЕАЛИЗАЦИИ ЭКОЛОГИЧЕСКИХ ПРОГРАММ (Journal of Economic Research & Business Administration, 2015)
The paper deals with the development of environmental programs and the way forward with them.